TATHWÎR AL-KITÂB AL-DIRÂSÎ LI 'ILMI AL-BALÂGHAH FÎ DHAUI AL-TADZAWWUQ AL-BALÂGHÎ LI AL-AHÂDÎTS AL-ARBA'ÎN AL-NAWAWIYAH - Haniah Haniah; Mohammad Ainin; Torkis Lubis (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
This study aims to: 1) reveal the literary language style in AlArbaeen by Imam Nawawi and the secrets behind it, 2) Extract and analyze the characteristics of the developed Bayan module. 3) Produce a Bayan textbook developed based on the study of AlArbaeen and reveal its influence for improving students; skill to understand and implement the Hadith in their daily life. The researcher used a qualitative descriptive research and development research method. The result of the research showed that there is found Bayani style in Arba'in hadith. Its beauty lies in the short, firm, hyperbolic expressions in expressing meaning, proper word choice and touching personification, depicted in terms of aqidah, shariah and morals. The developed textbook is characterized by a rhetorical appreciation of Arbain's hadith text without leaving an explanation of Balagah's rules. The Bayan Science textbook products developed are valid in terms of content, design and language.